Gendered Experiences of School Teachers: A Study in Government Schools in Delhi - MANDAL, MRINMAYEE; SRIVASTAVA, ANSHU (JOURNAL OF INDIAN EDUCATION, 2025)
This article is based on primary data collected in Delhi Government schools that point towards gendered practices and processes within the schools, and how the teachers navigate and negotiate with them. The school represents the microcosm of the society, and presents its own version of private and public spheres, within which the female and male teachers find themselves getting segregated, in terms of duties, responsibilities and key expectations. Through in-depth interviews and discussions with teachers across two government schools in Delhi, this study aims to highlight that the gendered structure, system and norms within a school, decided and actioned upon by the teachers, impact them as well as their worldview. The school cultures at both schools were found to reflect the inherent biases of the society, and creates a version of private and public spheres within the institutions that govern the interactions between the teachers and the spaces as well as their professional outcomes.